Incidence of epilepsy: a systematic review and meta-analysis. - Ngugi, A; Kariuki, S; Bottomley, C; Kleinschmidt, I; Sander, J; Newton, C (2011)
OBJECTIVE: To estimate the pooled incidence of epilepsy from published studies and investigate sources of heterogeneity in the estimates. METHODS: We searched online databases for incidence studies and used meta-analytic methods to analyze the data. RESULTS: Thirty-three articles met the entry criteria. The median incidence of epilepsy was 50.4/100,000/year (interquartile range [IQR] 33.6-75.6), while it was 45.0 (IQR 30.3-66.7) for high-income countries and 81.7 (IQR 28.0-239.5) for low- and middle-income countries. Population-based studies had higher incidence estimates than hospital-based studies (p = 0.02) while retrospective study design was associated with lower estimates than prospective studies (p = 0.04). CONCLUSION: We provide data that could potentially be used to assess the burden and analyze the trends in incidence of epilepsy. Our results support the need for large population-based incidence studies of epilepsy.